Using a Computational Grid for Geographic Information Analysis: A Reconnaissance. - Armstrong, Marc P.; Cowles, Mary Kathryn; Wang, Shaowen (Professional Geographer, 2005)
The writers overview the state of the practice in Grid computing, which links available, trusted computer systems via high-speed networks to form configurable, distributed virtual computing resources. They present project results that demonstrate how this new approach to computation can be utilized to address a spatial problem. They also comment on their current research on the development of grid portals, which are intended to help researchers access sets of easy-to-use distributed computing tools that can be configured into a domain-specific, problem-solving environment.